Zinc-Smelting Technology of China in the Ming and Qing Dynasties: The Smelting Furnaces. (2nd January 2023) - Xiao, Birui; Huang, Wan; Ma, Lingxiao; Li, Dadi; Bai, Jiujiang; Li, Yuniu
ABSTRACT: Academic discussion of traditional zinc-smelting technology in China has been hampered by a paucity of physical data recovered from early production sites. In recent years, however, the discovery of former zinc-smelting sites in the municipality of Chongqing in south-western China has provided important evidence from archaeological excavations that contribute to the study of this topic. Taking the smelting furnace found at the Linjiangerdui site in Zhong County as an example, this paper introduces and discusses the form, use and maintenance of the zinc-smelting furnace of the Ming Dynasty (AD 1368–1644), and makes a preliminary comparison with the smelting furnaces dating to the Qing Dynasty (AD 1636–1912) unearthed in Shizhu County and the mountainous Hunan Province in an attempt to elucidate the development and evolution of ancient Chinese zinc-smelting technology.